Accessibility of Political Participation for Different Abbility in The 2024 General Election in DKI Jakarta - Alemande, Deasy; Muslikhatul Ummah, Siti; Sugeng Priyanto, Agustinus; Sumantri Ms., Imam (Unnes Political Science Journal, 2024)
This research is motivated by the uneven socialization, the inaccessibility of polling stations, the absence of ballots with Braille templates, the lack of assistance for the visually impaired, and the increasing number of disabled voters in DKI Jakarta in the 2024 elections. The research results show that the accessibility for different abbility in DKI Jakarta during the 2024 elections has been adequately pursued by the General Elections Commision DKI Jakarta. The presence of assistance for disabled voters, socialization, the availability of Braille template ballots. Polling stations that are friendly to disabled voters. Driving and inhibiting factors in the accessibility of different abbility in the 2024 elections are as follows: the driving factor is the affirmative action taken by the General Election Commission regarding access for disabled voters. Meanwhile, the inhibiting factors are: uneven dissemination of information, lack of Braille template ballots at polling stations, and inadequate selection of polling station locations. The suggestion that can be given is the improvement of infrastructure at polling stations, The General Elections Commission DKI Jakarta can collaborate more with the disability community, and socialization is expanded in schools specifically for different ability, namely Special Schools (SLB).